Night sky - Sparrow, Giles, 1970- (New York : Scholastic, 2012)
An introduction to the stars and constellations, discussing the history of the starts, and includes brief information on the planets and moon.
Includes index.
7.1
5-8
Keywords: Constellations -- Juvenile literature; Planets -- Juvenile literature; Galaxies -- Juvenile literature; Constellations; Planets; Galaxies; Constellations; Planets; Galaxies